Vliv klíštěcích slin na vývoj zánětu indukovaného boreliemi v kůži myši - Štajnerová, Tereza (Jihočeská univerzita, 2018)
The aim of the thesis was to review the effects of tick saliva on borrelia-induced inflammatory response. We performed immunohistochemical analysis and histological staining with Mallory trichrome and hematoxylin-eosin of inflamed mouse skin after injection of Borrelia afzelii spirochetes combined with tick saliva.
Effect of tick saliva on the developement of borrelia-induced inflammation in mouse skin